Greek thought, Arabic culture : the Graeco-Arabic translation movement in Baghdad and early ʻAbbāsid society (2nd-4th/8th-10th centuries) - Gutas, Dimitri (Routledge, 1998)
"With the accession of the Arab dynasty of the 'Abbasids to power and the foundation of Baghdad, a Graeco-Arabic translation movement was initiated, and by the end of the tenth century, almost all scientific and philosophical secular Greek works that were available in late antiquity had been translated into Arabic. This book explores the social, political and ideological factors operative in early 'Abbasid society that sustained the translation movement."